An Epidemiological Study of Anemia and Renal Dysfunction in Patients Admitted to ICUs across the United States - Donald F. Brophy; Spencer E. Harpe; Daniel E. Carl; Gretchen M. Brophy (Anemia)
The aims of this study were to determine the associations between anemia of critical illness, erythropoietin stimulating agents (ESA), packed red blood cell transfusions and varying degrees of renal dysfunction with mortality, and ICU- and hospital length of stay (LOS). This was a cross-sectional retrospective study of 5,314 ICU patients from USA hospitals. Hospital, patient demographics, and clinical characteristics were collected. Predictors of mortality and hospital and ICU LOS were evaluated using multivariate logistic regression models. The mean ICU admission hemoglobin in this study was 9.4 g/dL. The prevalence of ESA use was 13% and was associated with declining renal function; 26% of the ICU patients in this study received transfusion. ESA utilization was associated with 28% longer hospital LOS (P<0.001). ICU LOS was increased by up to 18% in patients with eGFR rates of <30 and 30–59 mL/min/1.73 m2, respectively (P<0.05) but not in those receiving dialysis. Mortality was significantly associated with renal dysfunction and dialysis with odds ratios of 1.94, 2.66 and 1.40 for the dialysis, and eGFR rates of <30 and 30–59 and mL/min/1.73 m2, respectively (P<0.05). These data provide a snapshot of anemia treatment practices and outcomes in USA ICU patients with varying degrees of renal dysfunction.